Qingchang Huashi granule ameliorates experimental colitis via restoring the dendritic cell-mediated Th17/Treg balance - Jia Jia; Kai Zheng; Hong Shen; Jiangyi Yu; Ping Zhu; Shihai Yan; Yi Xu; Lei Zhu; Yuelin Lu; Peiqing Gu; Wan Feng (BMC, 2020)
Abstract Background The balance between T helper 17 (Th17) cells and regulatory T cells (Tregs) is involved in immunological tolerance. Destruction of immunological tolerance by dendritic cell (DC)-mediated T cells is involved in the pathogenesis of ulcerative colitis (UC). Qingchang Huashi granule (QCHS) has been confirmed in the treatment of UC involved by inhibiting the activation of DCs. The aim of this study was to investigate the mechanism through which QCHS restores the Th17/Treg balance by modulating DCs in the treatment of UC. Methods The effects of QCHS on Th17 cells, Tregs and DCs were detected in a 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced experimental colitis model. Furthermore, we injected QCHS-treated DCs into colitis model to test whether QCHS modulates the Th17/Treg balance via DCs. Tregs and Th17 cells were analyzed by FACS. IL-10, IL-17, and Foxp3 were measured by ELISA, Western blot and qRT-PCR. Results Both QCHS and QCHS-treated DCs improved colonic histopathology, diminished Th17 cell differentiation and inhibited IL-17 production while promoting CD4+CD25+Foxp3+ Treg differentiation and augmenting IL-10 and Foxp3 expression in colitis mice. Additionally, QCHS reduced CD86 and MHC-II expression on DCs, decreased IL-12 production ex vivo and restored the Th17/Treg ratio in the colitis model. Conclusion The findings of this study indicate that QCHS ameliorates TNBS-induced colitis by restoring the DC-mediated Th17/Treg balance.